An Analysis of the Impact on the Electricity Market of Fully Liberalizing the Power Generation and Utilization Plans for Operating Power Users. Issue 1 (July 2020) - Yang, Jianhua; Liu, Dunnan; Bai, Shunming; Li, Pengfei; Dong, Zhixin
Abstract: In June 2019, the National Development and Reform Commission announced the "Notice on the Requirements for fully liberalizing the power generation and utilization plans for operating power users", which means that the electricity generation plan for operational electricity users will be fully liberalized, except for residents and public utilities, other power users can participate in market-oriented power transactions. Therefore, it is urgent to study the impact of the introduction of policies on electricity market operations and electricity market transactions. First of all, this paper studies the process of opening up the electricity generation and utilization plans of foreign power users. Then, the impact of the policy on the electricity market is analyzed from the dimensions of market transaction size, market transaction entities, and market operation supervision. Finally, we analyzed the impact of the policy on the electricity market trading system from trading and management perspective.